Effects of COVID-19 restrictions on mechanization service providers and mechanization Equipment retailers: Insights from phone surveys in Myanmar - Takeshima, Hiroyuki; Masias, Ian; Win, Myat Thida; Zone, Phoo Pye (International Food Policy Research Institute, 2021)
COVID-19 continues to plague global food security not only directly through health effects but also indirectly through responses that restrict key economic functions of the agri-food sector. De-spite the growing literature on the effects of COVID-19 on the agri-food sector, evidence on cer-tain players like mechanization service providers (MSP) and mechanization equipment retailers (MER) remain scarce. This study provides insights into the effects of COVID-19 restrictions on MSP and MER in Myanmar, where the majority of MSP and MER are relatively new and poten-tially vulnerable to these economic shocks, using an unbalanced panel data from five rounds of phone surveys. We find that direct responses to COVID-19 involving movement restrictions, as well as disruptions in the market that led to increased cost and reduced availability of machinery and equipment, and growing financial challenges, had significantly negative effects on revenue prospects, service delivery, sales of machines and equipment by MSE and MER. Our analyses based on rare multi-round surveys during a single production season also reveal important dy-namics in MSP’s decision-making; negative revenue prospects at particular period can further hurt revenue prospects in subsequent periods, which is consistent with the hypotheses that agents like MSP who had incurred significant sunk-cost in machines can engage in more desperate and thus potentially suboptimal business practice to recover the sunk-cost. This may result in a vi-cious cycle of declining revenues in the future in the face of shocks like COVID-19. Overall, evi-dence suggests that, policies to minimize movement restrictions, various financial support, and mitigate any pessimism at the beginning of production season are all important to make sure MSP and MER continue to function effectively during the COVID-19 pandemic that persists in 2021.